The toxic mechanism and application of tetrodotoxin (TTX) - Zhang Xiaonan (MATEC Web of Conferences)
Tetrodotoxin (TTX) is a powerful toxin related to nerve cells that is commonly discovered at loads of puffer fish, and working out the best way of cooking, whereas keeping the flavour but getting rid of the toxicity has challenged people for decades, which removing the organ with toxin is currently most certified. In terms of mechanism of toxicity, binding with voltage-gated sodium channel in order to stop neuron transmission is usually what TTX does, and this action arises different symptoms from medium to severe. Death is not rare to see within severe reaction after ingestion of TTX, and there were plenty of researches studied on the lethal dose of TTX. Therefore, this research will analyze the toxicity mechanism of TTX and its application in treatment. Its special mechanism and non-addictive property allow it having a promising aspect regarding to medical treatment of pain related therapy or diseases. There is no limit to explore in these two areas, and investigation of working out mechanism of toxicology never stop.